A Cedar Cove Christmas - Macomber, Debbie (MIRA, 2008)
After a comedy of errors on Christmas Eve, a five-month pregnant woman, traveling to Cedar Cove to search for her child's father--who doesn't know she's pregnant--finds herself lodging in an apartment above a barn. The residents of Cedar Grove come to her rescue as an early labor begins.